Performance of a Patient Engagement App for Pre-Op Education [20G]. (May 2020) - Cherot, Elizabeth; Kett, Attila; Siddiqui, Zishan
Abstract : INTRODUCTION: Enhanced recovery after surgery is an innovation in perioperative care with the goal to achieve better patient engagement and improved outcomes like reduced opiate use and decreased hospital stay. Features are designed to accelerate patient recovery by reducing surgical stress and support physiologic function by allowing po intake shortly before surgery, multi-modal pain management, and early mobilization. Keys to success are patient education, engagement and self-efficacy. The program is dependent on assessing several patient reported care milestones like discontinuation of the Foley catheter, ambulation and pain scores. Because this is a human resource intensive endeavor, we developed an app with the goal of better engagement, education and response tracking while reducing human resources. METHODS: We deployed an app with the following components: multimedia education, reminders and check lists with the ability for patient reported data collection. Patients activated the app 3 weeks before surgery and used the tool for data collection pre and post operatively. We wanted to demonstrate patients consumed the educational content, responses to the surveys and compliance with our program preoperatively. RESULTS: We had 285 patients undergo ERAS program with 97.54% activation of our app before surgery, 92.86% response rate in the first week, 75.51% in the second week. 56.16% reported the app prevented 1 or more phone calls and 12.33% reported prevention of 1 or more visits to the hospital. CONCLUSION: We demonstrated both feasibility, high patient engagement and utilization for our app. One should consider using to unburdened staff and means to perform patient driven data collection.